VMware vSphere 6.7 data center design cookbook : over 100 practical recipes to help you design a powerful virtual infrastructure based on vSphere 6.7 /: over 100 practical recipes to help you design a powerful virtual infrastructure based on vSphere 6.7. (2019) - Brown, Mike; Cartwright, Hersey
No abstract available